Smoking-related knowledge, attitude and perception among young girls - Mohamad Noor, Zaswiza; Kaur, Swinder Jit; Nik Mohamed, Mohamad Haniki (2008)
Background: Cigarette smoking among youth is influenced by many factors such as advertising, the desire to rebel against authority, peers, weight, and addictiveness to nicotine. Studies have shown that adolescent and adult smokers do not fully appreciate the health consequences of smoking cigarettes. During 1993-2000, prevalence of current smokers reduced in all age groups, except those aged 18-24 years. Young adults continue to be an important target of tobacco industry marketing efforts. In Malaysia, smoking among female 13 to 18 years is 4.8% (NHMS 2, 1996). However, assessment of knowledge and perception regarding smoking in this group is lacking. Objective: To determine the smoking behavior among female adolescents, and to assess their smoking-related knowledge and perception. Method: 56 female adolescents selected randomly at a shopping mall were given questionnaires to self-administer upon consent. Questionnaires contain demographic data and 30 smoking-related questions. Data were analyzed descriptively using SPSS 12.0. Result: Mean age is 17.85 ± 1.1 (range 16 to 19) years old. 56 (100%) respondents admitted to tobacco use. 53.6% were light smokers, 14.3% moderate and 32.1% heavy smokers. 32% of the subjects smoked more than 20 sticks, 50% smoked 2-20 sticks and 18% smoked less than 2 sticks per day. 40% of them smoked everyday. 78% bought cigarettes from convenient stores or restaurants. 18% also tried shisha, bidis, cigars and chewing tobacco.66% smoked at public area and 62.5% smoked without family acknowledgement. 21.4% believed will still smoke in the next 5 years. 69.6% agreed that quitting is difficult. 71.4% agreed smoking makes appearance less attractive. Only 23.2% thought smoking makes one become more outstanding. 55.4% disagreed that smoking reduces their weight vs. 42.9% who agreed. 91.1% realized inhaling other person’s tobacco smoke is harmful. Only 23.2% admitted that smoking is wasteful. 87.5% agreed with the ‘No Smoking’ signs at the public places. 60.7% wanted to quit smoking if possible. Conclusion: Smoking among young female adolescents in Malaysia is a serious problem Adolescent smokers need to be educated further regarding the harmfulness of smoking and provided assistance with quitting.